The business impact analysis of the minimum wage valorisation - Pernica, Martin (Business: Theory and Practice, 2017)
The paper presents the results of research conducted in companies based in the South Moravian Region with the aim to gain information concerning the influence of minimum wage on employment and competitiveness of business. To complete this paper there have been used methods of analysis, comparison, induction and deduction, percentage of positive and negative answers and Pearson’s chi-squared test. The research revealed that majority of companies would embrace minimum wage derived from average wage and yearly minimum wage inflation adjustment. Although, approximately one half of the respondents believe that the minimum wage makes it harder to employ low-skilled workers.